What Did the Multicultural Policies of the Last Century Promise that Need to Be Re-Imagined in Today’s DEDI Post-Secondary World? - James, Carl E. (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2023)
This article is an expanded version of the 2023 Plenary Lecture at the Canadian Society for the Study of Education (CSSE) Conference held at the Congress of the Humanities and Social Sciences. This invited essay explores the extent to which the promise of DEDI’s (decolonization, equity, diversity, and inclusion) polices and initiatives might bring about the imagined institutional changes in today’s context. Contending that we have been here before, the essay reckons that changes will not come about simply through verbal rhetoric, targeted hiring, or training sessions where individuals engage in self-reflection on their attitudes, values, and behaviours, but through critical examination of institutional policies, programs, and practices that result in the removal of systemic barriers which have operated over the years to maintain the inequitable situation being addressed.